Hubungan antara Harga Diri dengan Kesepian pada Mahasiswa Perantau - Dias Amaliah Kangiden; Raja Oloan Tumanggor (Lembaga Yasin AlSys, 2026)
Migrant students are a group vulnerable to psychological challenges arising from adaptation to a new environment, separation from family, and changes in social networks, which can elicit feelings of loneliness when needs for emotional closeness and social support are not met. One psychological factor presumed to contribute to loneliness among migrant students is self-esteem, defined as an individual’s evaluation of their worth and value. This study aimed to examine the relationship between self-esteem and loneliness among migrant students. Using a quantitative correlational method, the study involved 355 participants aged 18–25 years who were studying at Universitas X. Self-esteem was measured using the Rosenberg Self-Esteem Scale (RSES), and loneliness was measured using the UCLA Loneliness Scale Version 3. Because the data were not normally distributed, Spearman’s rho correlation was used for analysis. The results showed a strong negative relationship between self-esteem and loneliness (r = -0.873; p < 0.001), indicating that higher self-esteem was associated with lower loneliness among migrant students, and vice versa. Descriptive analysis also indicated that self-esteem was in the moderate category, whereas loneliness was in the high category. These findings underscore the importance of attending to self-esteem in understanding and reducing loneliness among migrant students facing adaptation pressures in higher education settings.